Peutz-Jegher’s syndrome presenting as jejunoileal intussusception in an adult male: a case report - Thakker, Hardik H (Cases Network Ltd, 2009)
INTRODUCTION: Peutz-Jegher’s syndrome is a rare autosomal dominant disorder that typically manifests itself as recurrent colicky abdominal pain and blood loss in stools. In adults, it is only rarely accompanied by frank intussusception and intestinal obstruction. We encountered an adult Asian Indian male who presented with an intestinal obstruction due to jejunoileal intussusception. It was caused by a 3.5 cm large hamartomatous polyp of Peutz-Jegher’s syndrome. We feel reporting the unusual presentation of this rare condition may be a noteworthy contribution to the scarce literature on Peutz-Jegher’s syndrome from India. The case report may be of educational importance to the clinicians and students because it is unusual to see this case in typical clinical practice. CASE PRESENTATION: A 38-year-old Asian Indian male presented to us in the surgical emergency room with colicky abdominal pain, reporting vomiting and blood in stools over the previous two days. Clinical examination suggested intestinal obstruction. Ultrasonography of the abdomen showed signs of intussusceptions, which were then confirmed by an emergency exploratory laparotomy. We resected the intussuscepted small bowel segment and performed a jejuno-ileal anastomosis. A histopathology examination of the resected specimen revealed multiple hamartomatous polyps suggestive of Peutz-Jegher’s syndrome. In this case report, we present the pathology findings, their clinical correlation and a detailed discussion of Peutz-Jegher’s syndrome and adult intussusception. We also discuss its other rare presentations reported in literature. CONCLUSION: Hamartomatous polyps of Peutz-Jegher’s syndrome can sometimes grow to a large size and form the lead point of an intussusception.